Qualidade, compostos bioativos e atividade antioxidante de uva ‘Isabel’ submetida na pré-colheita à aplicação de cloreto de cálcio e elicitor à base de biomassa cítrica - Santos, Leonardo da Silva (2017)
Grape postharvest conservation intended for fresh consumption is directly related to all stages of the productive chain, being necessary an appropriate handling during harvest. Currently, it is seeking to extend the postharvest life of fruit by techniques that maintain the highest quality for consumption until the product reaches the consumer's table. Thus, a set of pre-harvest technologies, when properly applied, extends the postharvest life and maintains the desirable characteristics of the product in postharvest. Thus, the objective of this study was to evaluate the influence of the pre-harvest application of calcium chloride and an elicitor based on citric biomass in 'Isabel' grapes and its effects on the maintenance of postharvest quality, showing the main changes in quality attributes and bioactive compounds during storage. The experiment was conducted in a commercial vineyard aged three years located in the Chã dos Esquecidos roral área, located at São Vicente Férrer municipality, situated in the Vally of Siriji river, Pernambuco state, Brazil. It was used grape plants of the 'Isabel' cultivar and the treatments were applied using a built-up pressure sprayer with a trigger coupled in a PET bottle, which applied the treatments targeting the grape´s clusters in the plant 21 days before harvest. The experimental design in the fild was a randomized block, composed of four treatments: elicitor based in citric biomass (BC), elicitor based in Biomass Citric + CaCl2 (BC + C), CaCl2 (C), and control (T), plants without application. Twenty one days after application, the grapes were harvested in the morning, in the commercial maturity stage and transported to the Laboratorio de Biologia e Tecnologia Pós-colheita, CCA-UFPB, where three clusters were selected and separated by repetition based on the blocks from the field, for each treatment. Clusters were placed in polystyrene trays and packed in modified atmosphere (wrapped with PVC film (polyvinyl chloride of 17 microns) and ambient atmosphere (without film) and stored under ambient conditions (25 ± 2 °C and 75 ± 2% UR) for up to 12 days, wih evaluations at 0, 2, 4, 6, 8, 10, and 12 days. The use of elicitor based on Citrus Biomass decreased the loss of mass. The pre-harvest application of CaCl2 and elicitor based on Citrus Biomass reduced 'Isabel' grape drop of during storage. The use of the elicitor based on Citrus Biomass in 'Isabel' grapes reduced the incidence of postharvest decay. The use of the elicitor based on Citrus biomass + CaCl2 increased anthocyanin content. The skin of 'Isabel' grape presented polyphenol content and antioxidant activity greater than the pulp.